UJI AKTIFITAS BIOLOGIS EKSTRAK KULIT DAN DAGING BUAH MAJA (Aegle marmelos (L.) Corr) DENGAN METODE BRINE SHRIMP LETHALITY TEST - Devi Ratnawati (Molluca Journal of Chemistry Education (MJoCE), 2012)
A study concerning the test phytochemical extracts of fruit peel and pulp magazine (Aegle Marmelos) as well as the biological activity test with brine shrimp lethality test method. The purpose of this study was to determine the presence or absence of secondary metabolites contained in the skin and pulp magazine. The study consisted of two phases: first, a preliminary test the secondary metabolites (flavonoids, alkaloids, steroids and triterpenoids), which both the biological activity assay using Artemia salina leach shrimp larvae. The results showed that only maja fruit skin extracts containing secondary metabolites are alkaloids and triterpenoids with high levels of (+), while the pulp magazine did not show a positive test to the test of secondary metabolites. The test results of the biological activity of fruit peel extract maja has a value of 68.07 ppm LC50, whereas extracts pulp magazine has a LC50 value 47.97 mg / L